An ACE2-Alamandine Axis Modulates the Cardiac Performance of the Goldfish Carassius auratus via the NOS/NO System - Mariacristina Filice; Rosa Mazza; Sandra Imbrogno; Olga Mileti; Noemi Baldino; Amilcare Barca; Gianmarco Del Vecchio; Tiziano Verri; Alfonsina Gattuso; Maria Carmela Cerra (MDPI AG, 2022)
Alamandine is a peptide of the Renin Angiotensin System (RAS), either generated from Angiotensin A via the Angiotensin Converting Enzyme 2 (ACE2), or directly from Ang-(1-7). In mammals, it elicits cardioprotection via Mas-related G-protein-coupled receptor D (MrgD), and the NOS/NO system. In teleost fish, RAS is known to modulate heart performance. However, no information is available on the presence of a cardioactive ACE2/Alamandine axis. To fill this gap, we used the cyprinid teleost Carassius auratus (goldfish) for in silico and in vitro analyses. Via the NCBI Blast P suite we found that in cyprinids ace2 is phylogenetically detectable in a subcluster of proteins including ace2-like isoforms, and is correlated with a hypoxia-dependent pathway. By real-time PCR, Western Blotting, and HPLC, ACE2 and Alamandine were identified in goldfish heart and plasma, respectively. Both increased after chronic exposure to low O2 (2.6 mg O2 L−1). By using an ex-vivo working goldfish-heart preparation, we observed that in vitro administration of exogenous Alamandine dose-dependently stimulates myocardial contractility starting from 10−11 M. The effect that involved Mas-related receptors and PKA occurred via the NOS/NO system. This was shown by exposing the perfused heart to the NOS inhibitor L-NMMA (10−5 M) that abolished the cardiac effect of Alamandine and was supported by the increased expression of the phosphorylated NOS enzyme in the extract from goldfish heart exposed to 10−10 M Alamandine. Our data are the first to show that an ACE2/Alamandine axis is present in the goldfish C. auratus and, to elicit cardiac modulation, requires the obligatory involvement of the NOS/NO system.